Faktor-Faktor Pencegahan Fraud pada Lembaga Perbankan - Dewi, Putu Purnama; Suwantari, Ni Putu Eni; Pradhana, I Putu Dharmawan (E-Jurnal Akuntansi; Vol 31 No 6 (2021)DO - 10.24843/EJA.2021.v31.i06.p19, 2021)
The purpose of this study is to identify the factors that influence the prevention of fraud in banking institutions including the implementation of good corporate governance, the application of the tri hita karana culture and the existence of a whistleblowing system. The location of this research is the Regional Development Bank (BPD) Bali with a population of all staff of BPD Bali Renon branch with a total sample of 96 respondents and using the saturated sample method. The analysis technique applied is multiple linear regression analysis. The findings in this study illustrate that the implementation of good corporate governance, the application of the tri hita karana culture, and the whistleblowing system in the company illustrates a significant positive effect on fraud prevention efforts at Bank BPD Bali. Keywords: Good Corporate Governance; Tri Hita Karana Culture; Whistleblowing System; Fraud Prevention.